Peters world map : Pacific centered / Arno Peters - Peters, Arno; (Oxford, UK : Oxford Cartographers, 2004)
"One square centimetre on the map = 123,000 square kilometres in nature."; "An equal-area map."; "Map which represents countries accurately according to their surface area." Color; 1:25,000,000